Biological kinetics parameters in a pure culture biofilm developed in an airlift reactor - Lopes, F. A. (2000)
A diffusion-reaction model was fitted to data obtained with Pseudomonas fluorescens biofilms developed in an airlift reactor under different limiting substrate conditions, in order to determine the biofilm kinetic constants and the substrate concentration profiles within the biological films. Model predicted concentration profiles within the biofilms demonstrate that all films were completely penetrated by the substrate and that the reaction rate inside the biofilms was of zero order. The estimated kinetic constants (μmax = 0.24 h-1; Ks = 0.73x10-3 kg/m3) differ from those obtained in a suspended culture (μmax= 0.31 h-1; Ks = 6.21 kg/m3), as a result of the different metabolic state of microorganisms within biofilms.